The reconstruction of the public administration, the state commissions, and the role of the new cadres of specialists during the post-revolution in Mexico - Uhthoff López, Luz María (2017)
This paper examines the role of the Petroleum Technical Commission (1915) and the Commission for Administrative and Financial Reorganization (1917) in the definition of post-revolutionary public administration. As is well known, administrative modernization and the formulation and implementation of economic policy in modern states were linked to the formation of technical and bureaucratic cadres, and to the development of the latest trends in economic and administrative knowledge, so that our interest is to understand how this process was carried out in the construction of a new administration, after the revolutionary process begun in 1910.